High heterogeneity of HIV-related sexual risk among transgender people in Ontario, Canada: a province-wide respondent-driven sampling survey - Bauer Greta R; Travers Robb; Scanlon Kyle; Coleman Todd A (BMC, 2012)
Abstract Background Studies of HIV-related risk in trans (transgender, transsexual, or transitioned) people have most often involved urban convenience samples of those on the male-to-female (MTF) spectrum. Studies have detected high prevalences of HIV-related risk behaviours, self-reported HIV, and HIV seropositivity. Methods The Trans PULSE Project conducted a multi-mode survey using respondent-driven sampling to recruit 433 trans people in Ontario, Canada. Weighted estimates were calculated for HIV-related risk behaviours, HIV testing and self-reported HIV, including subgroup estimates for gender spectrum and ethno-racial groups. Results Trans people in Ontario report a wide range of sexual behaviours with a full range of partner types. High proportions - 25% of female-to-male (FTM) and 51% of MTF individuals - had not had a sex partner within the past year. Of MTFs, 19% had a past-year high-risk sexual experience, versus 7% of FTMs. The largest behavioural contributors to HIV risk were sexual behaviours some may assume trans people do not engage in: unprotected receptive genital sex for FTMs and insertive genital sex for MTFs. Overall, 46% had never been tested for HIV; lifetime testing was highest in Aboriginal trans people and lowest among non-Aboriginal racialized people. Approximately 15% of both FTM and MTF participants had engaged in sex work or exchange sex and about 2% currently work in the sex trade. Self-report of HIV prevalence was 10 times the estimated baseline prevalence for Ontario. However, given wide confidence intervals and the high proportion of trans people who had never been tested for HIV, estimating the actual prevalence was not possible. Conclusions Results suggest potentially higher than baseline levels of HIV; however low testing rates were observed and self-reported prevalences likely underestimate seroprevalence. Explicit inclusion of trans people in epidemiological surveillance statistics would provide much-needed information on incidence and prevalence. Given the wide range of sexual behaviours and partner types reported, HIV prevention programs and materials should not make assumptions regarding types of behaviours trans people do or do not engage in.